The Role of School Feeding program supported by DAL Company in Students’ Enrolment and Drop-out - Ibrahim, Hind Bushra Ahmed (Advances in Social Sciences Research Journal, 2017)
School feeding program as a social safety net has been popular in developing countries as an instrument for achieving the Millennium Development Goals. These programs are frequently targeted towards families’ low socioeconomic status and unable to send their children to school or face poor attendance and drop-out from school .In the present study an attempt has been made to analyse the role of school feeding program supported by DAL Company in students’ enrollment and Drop-out in Ombadda Locality ( Alamal and Ahmad AlrdeeGaber school). The results showed that majority of the students’ parents were suffering formal education, worked in the informal sector to support their families. All teachers and students’ parents considered the most frequent reasons for dropping out of or not enrolling in school are the poor financial standing of the family. Also, all of them agreed upon DAL school feeding program have positively impact on educational attainment by increasing enrolment, attendance and reduced students’ drop-out.